Utilization of Red Dragon Fruit Peel Extract (Hylocereus polyrhizus sp) in Cinnamon Boba - Rizka Larasati Putri; Dwi Agustiyah Rosida; Tiurma Wiliana Susanti Pandjaitan (Agricultural Science, 2022)
A popular boba is the “brown sugar” boba which is dark brown. Boba can be made with different color variations, one of which is red dragon fruit skin because it contains anthocyanins that can be used as natural dyes. It also contains high enough antioxidants, so it is good for health. Unfortunately, it has a less favorable aroma and taste, so adding other mixtures such as cinnamon with a distinctive taste and aroma is necessary. This study aims to determine the panelists' preference for cinnamon boba with the addition of red dragon fruit peel extract. Descriptive research with an experimental approach to produce products with different compositions and organoleptic tests to determine the panelists' preference for products has been used in this study. The mixed formulas of red dragon fruit peel extract with water used were P0 (red dragon fruit peel extract 0 g, 250 ml water), followed by P1 (50 g, 200 ml), P2 (100 g, 150 ml), P3 (150 g, 100 ml) and P4 (200 g, 50 ml). Then, the preference test was carried out on 30 panelists related to color, aroma, taste, and texture with the rating categories of strongly dislike (1), dislike (2), quite like (3), like (4), and very like (5). The results showed that the higher the red dragon fruit peel extract content, the more favorable the color produced; The level of preference for aroma and taste was relatively the same in all treatments, and the P3 treatment produced the most preferred texture.